2009
DOI: 10.3201/eid1502.080006
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria, Zambia

Abstract: Clinical relevance of nontuberculous mycobacteria (NTM) isolated from 180 chronically ill patients and 385 healthy controls in Zambia was evaluated to examine the contribution of these isolates to tuberculosis (TB)-like disease. The proportion of NTM-positive sputum samples was signifi cantly higher in the patient group than in controls; 11% and 6%, respectively (p<0.05). NTM-associated lung disease was diagnosed for 1 patient, and a probable diagnosis was made for 3 patients. NTM-positive patients and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 23 publications
7
57
1
1
Order By: Relevance
“…The role of NTMs in the aetiology of TB-like syndromes has not been clearly elucidated in sub-Saharan African countries: a recently published comparative study supports a significant contribution [12]. In our series, a considerable proportion of NTMs were identified among both HIV-infected and uninfected chronic TB cases.…”
Section: Mgit960supporting
confidence: 53%
“…The role of NTMs in the aetiology of TB-like syndromes has not been clearly elucidated in sub-Saharan African countries: a recently published comparative study supports a significant contribution [12]. In our series, a considerable proportion of NTMs were identified among both HIV-infected and uninfected chronic TB cases.…”
Section: Mgit960supporting
confidence: 53%
“…This may not necessarily be due to a low incidence of NTM disease in developing countries, but rather result from less priority being given to NTM in regions where the TB burden is overwhelming. Buijtels et al [11] reported that in Zambia, a country with a high prevalence of TB, MAC was the most frequently isolated NTM. Similarly, a study identifying NTM from clinical specimens in Ethiopia showed MAC to be the predominant species, followed by M. abscessus, M. gordonae, M. simiae and M. fortuitum.…”
Section: Discussionmentioning
confidence: 99%
“…Not all acid-fast bacilli represent the M. tuberculosis complex. Non-tuberculous mycobacteria [18] and some other bacterial species including Nocardia species which are widespread19 yield positive results in ZN smear detection of acid-fast bacilli (AFB). For instance, in the present study, 4.2% (15/361) of the mycobacterial disease cases were NTM cases.…”
Section: Discussionmentioning
confidence: 99%